The Art of Poetry and the Art of Memory: Philip Sidney’s Mnemonic Poetics - Helfer, Rebeca (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2022)
This article explores the significance of the art of memory as a mnemonic poetics in Philip Sidney’s literary theory and practice. The art of memory is more than an ancient mnemonic method, I argue; rather, it constitutes a poetics that evolves from Plato to Petrarch as part of an interdisciplinary dialogue and debate about how the past is remembered (particularly through love stories) and remade in the present. This tradition of mnemonic poetics is central to Sidney’s portrayal of the art of poetry as an art of memory in his Apology for Poetry, a tradition that Sidney remembers anew in his sonnet sequence, Astrophil and Stella. Sidney constructs his poem as a memory theatre in which he demonstrates and indeed dramatizes the art of memory indirectly and ironically: through a poetic persona, Astrophil, who longs for an “art of forgetting” in his pursuit of originality.